2014
DOI: 10.1136/bjsports-2014-093494.152
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Injuries in Contact Flag Football

Abstract: Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på journals.lww.com: http://dx.doi.org/10.1097/JSM.0b013e3182694870 This is the final text version of the article, and it may contain minor differences from the journal's pdf version. The original publication is available at journals.lww.com: http://dx.doi.org/10.1097/JSM.0b013e3182694870 Main Outcome Measures: All time-loss injuries sustained in game sessions were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…In the intervention cohort, there were no injuries that resulted from fingers being caught in the opposing players' pockets. This can be compared to hand/wrist injuries in the historical cohort, of which 40% were caused by pockets (Fig.2) [15]. Thus, the no-pocket rule proved beyond reasonable doubt that it is a significant factor in reducing hand/wrist injuries in flag football.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In the intervention cohort, there were no injuries that resulted from fingers being caught in the opposing players' pockets. This can be compared to hand/wrist injuries in the historical cohort, of which 40% were caused by pockets (Fig.2) [15]. Thus, the no-pocket rule proved beyond reasonable doubt that it is a significant factor in reducing hand/wrist injuries in flag football.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies in flag football have shown a high percentage of anatomical specific injuries; the hand/wrist (16-34%), the knee (11-18%), the ankle (8-17%), the face and head (18-29%), and the shoulder (9-10%) [4,6,15,16]. Direct trauma was responsible for the vast majority of injuries (64-75%).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…A United States Air Force (USAF) 10‐year review (1993–2002) found American flag football to be the eighth highest non‐combat cause of lost workdays among active duty personnel . A report of an Israeli amateur league found that 30% of all injuries were of the digits or wrist and 40% of these were sustained during a tackle, when caught in another players clothing . To date, the only reference to the game in Australian medical literature is Baba et al .…”
Section: Introductionmentioning
confidence: 99%